Euglycemic Diabetic Ketoacidosis after a Single Dose of Empagliflozin in a Patient with Pancreatitis - Marta Brandão Calçada; Luís Fernandes; Rita Soares Costa; Sara Montezinho; Filipa Martins Duarte; Luísa Frutuoso; Ana Raquel Freitas (Clinics and Practice, 2021)
Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are the most recently approved drug class for the treatment of type 2 diabetes mellitus (T2D). Although they are largely well-tolerated, their intake has been associated with euglycemic diabetic ketoacidosis (DKA) in some rare cases. We report the case of a 70-year-old male with type 2 diabetes and no history of DKA, who started therapy with empagliflozin one day before presenting with acute pancreatitis and laboratory findings consistent with euglycemic DKA. SGLT2i can induce euglycemic DKA from the first dose. Given the atypical presentation, a high degree of clinical suspicion is required to recognize this complication.